Influence of Functional Group Modification on the Toxicity of Nanoplastics - Zhang, Haihong; Cheng, Haodong; Wang, Yudi; Duan, Zhenghua; Cui, Wenjie; Shi, Yansong; Qin, Li (Frontiers in Marine Science, 2022)
Nanoplastics (NPs) are ubiquitous in harvested organisms at various trophic levels, and more concerns on their diverse responses and wide species-dependent sensitivity are continuously increasing. However, systematic study on the toxic effects of NPs with different functional group modifications is still limited. In this review, we gathered and analyzed the toxic effects of NPs with different functional groups on microorganisms, plants, animals, and mammalian/human cells in vitro. The corresponding toxic mechanisms were also described. In general, most up-to-date relevant studies focus on amino (−NH2) or carboxyl (−COOH)-modified polystyrene (PS) NPs, while research on other materials and functional groups is lacking. Positively charged PS-NH2 NPs induced stronger toxicity than negatively charged PS-COOH. Plausible toxicity mechanisms mainly include membrane interaction and disruption, reactive oxygen species generation, and protein corona and eco-corona formations, and they were influenced by surface charges of NPs. The effects of NPs in the long-term exposure and in the real environment world also warrant further study.